2022
DOI: 10.1590/s1678-9946202264023
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum merozoite surface protein 3 as a vaccine candidate: a brief review

Abstract: Despite the many efforts of researchers around the world, there is currently no effective vaccine for malaria. Numerous studies have been developed to find vaccine antigens that are immunogenic and safe. Among antigen candidates, Plasmodium falciparum merozoite surface protein 3 (MSP3) has stood out in a number of these studies for its ability to induce a consistent and protective immune response, also being safe for use in humans. This review presents the main studies that explored MSP3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…This is a group of transport proteins which includes the PfMDR1 protein, and polymorphisms in the ABC transporters have been involved in anti-malarial drug resistance 30 . PfMSP3 is a merozoite surface protein and is a potential vaccine candidate 31 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a group of transport proteins which includes the PfMDR1 protein, and polymorphisms in the ABC transporters have been involved in anti-malarial drug resistance 30 . PfMSP3 is a merozoite surface protein and is a potential vaccine candidate 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Since 1994, it was discovered that MSP3-protective antibodies could be discovered in animals and humans. Later in 2003 and 2009, promising findings were obtained in preclinical and phase I clinical trial of the GMZ2 recombinant vaccine (containing MSP3 and glutamate-rich protein, GLURP), and further studies more emphasized on the potency of this MSP3-based vaccine candidates [ 71 ]. Previously, MSP4 was found to be immunogenic in nature both during natural infection and in laboratory animals, with limited gene polymorphism which simplifies the vaccine formulations [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study, using CHMI by intravenously injecting live P. falciparum sporozoites (PfSPZ Challenge) to assess vaccine efficacy, showed that the use of the novel adjuvant CAF01 did not significantly affect vaccine efficacy [132]. Despite being immunogenic, MSP3-based vaccines face significant challenges in achieving improved protective efficacy [133].…”
Section: Msp3 and Gmz2mentioning
confidence: 99%